Association Between Different Domains of Physical Activity and Body Adiposity Indicators in Breast Cancer Survivors - Silva, Daniela Tanajura Caldeira [UNESP]; Vanderlei, Luiz Carlos Marques [UNESP]; Palma, Mariana Romanholi [UNESP]; Ribeiro, Fernanda Elisa [UNESP]; Tebar, William Rodrigues [UNESP]; Tosello, Giuliano Tavares; Christofaro, Diego Giulliano Destro [UNESP] (Elsevier, 2021)
Background: To analyze the relationship between different physical activity (PA) domains and adiposity indicators in breast cancer survivors. Methods: This is a cross-sectional study, composed of 115 breast cancer (BC) survivors. Measurements of weight, height, waist circumference (WC), and hip circumference were objectively collected, as well as the analysis of body fat percentage through bioelectrical impedance analysis. The PA level was assessed by the Baecke questionnaire including domains related to occupational activity, leisure-time activity, and transportation, while the time spent in sedentary behavior was assessed through self-reported screen-time. Socioeconomic status was assessed through the Brazilian criteria for economic classification and considered as a covariate. Results: BC survivors with higher PA levels in leisure-time activity/sport presented reductions in body fat percentage (β = 1.13%; CI = -2.06; -0.21), BMI (β = 0.80 kg/m²; CI = -1.50; -0.11), WC (β = 1.89 cm; CI = -3.54; -0.23), and waist-to-height ratio (β = 0.13 cm; CI = -0.23; -0.02). Similar values were observed in PA during transportation and in total. There was no correlation between PA at work and adiposity indicators. Conclusion: Different PA domains were inversely related to body adiposity in BC survivors.
Keywords: Body composition; Breast neoplasms; Motor activity; Survivors; Women